Risk factors for progression to type 2 diabetes in prediabetes: a systematic review and meta-analysis - Shengying Hu; Wenting Ji; Yizhu Zhang; Wendi Zhu; Hongyu Sun; Yumei Sun (BMC Public Health)
Abstract Background Prediabetes is the earliest identifiable stage of glycemic dysregulation, and its progression can be delayed by effective control of risk factors. Currently, various risk factors for the progression from prediabetes to type 2 diabetes mellitus (T2DM) need to be further summarized. Objective This systematic evaluation of the risk factors for the progression of prediabetes to type 2 diabetes mellitus provides a theoretical basis for early recognition and intervention. The meta-analysis identifies the Fatty Liver Index as a significant risk factor [OR = 6.14, 95% CI (5.22, 7.22)] for the progression from prediabetes to type 2 diabetes, highlighting its predictive value. Methods PubMed, Web of Science, Embase, The Cochrane Library, CNKI, WANFANG, and VIP databases were searched to collect cohort studies on risk factors for progressing to type 2 diabetes in prediabetes from inception to February 15, 2024. STATA 17.0 was used for Meta-analysis. Results A total of 59 studies were included, all of which were of medium to high quality. The factors were categorized into four major groups: sociodemographic factors, lifestyle factors, psychosocial factors, and comorbidities and clinical indicators. Meta-analysis results showed that sociodemographic factors [age [OR = 1.03, 95% CI (1.01, 1.04)], family history [OR = 1.48, 95% CI (1.36, 1.61)], male sex [OR = 1.13, 95% CI (1.08, 1.19)], high BMI [OR = 1.21, 95% CI (1.15, 1.27)], high waist circumference [OR = 1.49, 95% CI (1.23, 1.79)], and high waist-to-hip ratio [OR = 2.44, 95% CI (2.17, 2.74)]]. Lifestyle factors included a lack of physical exercise [OR = 1.86, 95% CI (1.19, 2.88)], smoking [OR = 1.31, 95% CI (1.22, 1.41)], and moderate physical activity [OR = 0.24, 95% CI (0.09, 0.67)]. Psychosocial factors included anxiety [OR = 2.61, 95% CI (1.36, 5.00)], depression [OR = 1.88, 95% CI (1.35, 2.61)], and social deprivation level 4 [OR = 1.15, 95% CI (1.13, 1.18)]. Comorbidities and clinical indicators included hypertension [OR = 1.41, 95% CI (1.33, 1.50)], high triglycerides [OR = 1.25, 95% CI (1.10, 1.43)], high cholesterol [OR = 1.09, 95% CI (1.06, 1.12)], fatty liver index [OR = 6.14, 95% CI (5.22, 7.22)], low HDL-C [OR = 1.13, 95% CI (1.09, 1.36)], and high blood glucose levels [OR = 1.01, 95% CI (1.01, 1.02)]. Conclusions This study found that age, male sex, positive family history of type 2 diabetes, high BMI, unhealthy lifestyle, anxiety, depression, high blood pressure, high triglycerides, and a high fatty liver index are risk factors for the progression from prediabetes to type 2 diabetes and should be given sufficient attention. Moderate physical activity and Low HDL-C are protective factors. Future studies should also increase follow-up, explore the best diagnostic criteria for prediabetes, and fully consider the definitions of various factors. The study was registered in PROSPERO (CRD42024513931).